Evaluation of internal control: Are the judgements of external and internal auditors similar? - Haron, Hasnah; Zainuddin, Yuserrie; Ismail, Ishak (Universiti Utara Malaysia, 1999)
Evaluation of the internal control system is a critical area in which the duties of internal and external auditors overlap. Internal auditors design and maintain internal controls which are evaluated, and often relied upon by external auditors. Both groups of professionals should be interested in any systematic differences, which may exist between their judgement practices. Specifically, this study examines whether internal auditors as a group, make similar judgements as external auditors. The study was conducted by means of a questionnaire which includes a brief description of the internal control environment of a hypothetical company. A pre-answered internal control questionnaire for a payroll internal control system was included. Each auditor receives six similar cases to test for judgement consensus and two repeat cases to test for judgement consistency. Both the repeat cases are unique for each auditor. h e of them follows the 1/4 replicate of 28 design and the other is a repeat of the case The case, which follows the experimental design, is used to determine the judgement model of each group of external and internal auditors. The final judgement model was able to explain 39.8% of the judgements of external auditors and 37.4% of judgements of the internal auditors. The overall conclusion was that judgements of both external and internal auditors were quite similar to each other in their ratings of the internal control strength of a given system.